Estimasi kedalaman batuan dasar berdasarkan nilai tahanan jenis menggunakan metoda geolostrik konfigurasi Schlumberger di Universitas Negeri Padang di kampus Air Tawar (The estimation of the bedrock depth based on the resistivity value using the geolostric method of the Schlumberger configuration at Universitas Negeri Padang Air Tawar) - Nelvira Rizalmi; - Akmam; - Mahrizal (Department of Physics – Universitas Negeri Padang UNP, 2013)
The purpose of this study were determine the value of resistivity and the depth of basement rocks at Universitas Negeri Padang Air Tawar Campus, know the type of basement rocks at Universitas Negeri Padang Air Tawar Campus. The research was conducted using geoelectric method Schlumberger configuration. Measurements were taken at four-track measurements. 2D inversion results using the standard software v3.57 Res2Dinv constraint least squares inversion is suspected basement rocks on Line 2nd and Line 3rd. Line 2nd with the main sounding point located at coordinates 00053'53,1